International transmission of conventional and unconventional monetary policy and financial stress shocks from the euro area to Russia - Silvo Dajčman; Alenka Kavkler; Sergey Merzlyakov; S. Ė. Pekarskij; Dejan Romih (Journal of Central Banking Theory and Practice, 2022)
This paper studies the international transmission of the euro area's monetary policy and financial stress to Russia. The results show that financial stress in the euro area damages Russian economic activity and stock prices, but not its trade balance. The contractionary euro area monetary policy shock decreases Russian GDP, leads to real appreciation of the euro against the Russian rouble, damages Russian stock prices, but does not significantly affect the trade balance between countries. We also found that the Central Bank of the Russian Federation adjusts to monetary policy shocks in the euro area.
Keywords: E52; F42; G15; 330; conventional monetary policy; unconventional monetary policy; financial stress; Russia; international transmission